The Size and Shape of IPB Chickens and Kampong Chickens in Relation to Natural Selection (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2026)
IPB D1 chickens have been shown to exhibit superior growth and reproductive performance in comparison to kampong chickens, as demonstrated in previous studies. The selection of IPB D1 chickensresulted in the generation of IPB D2 and IPB D3 chickens. The objective of this study is to make acomparative analysis of the size and body shape of kampong chickens, IPB D1 chickens, IPB D2 chickens,and IPB D3 chickens. This analysis will be based on crowd diagrams during the starter and growerperiods. The present study employed Principal Component Analysis (PCA) based on measurements ofeight linear body surface area variables, including femur length, tibia length, tarsometatarsus length,tarsometatarsus circumference, third toe length, wing length, maxilla length, and comb height. Thesevariables are closely related to adaptive ability, resulting from natural selection. The selection of chickensbased on eight linear body surface area, in conjunction with natural selection, has been demonstratedto enhance chicken productivity. The analysis results demonstrate that IPB D1 and IPB D2 cocks, andIPB D2 and IPB D3 hens, in the starter period exhibit comparable body shapes, suggesting a relativelyuniform morphological pattern resulting from shared direction of selection. During the grower period,disparities in the direction of selection became evident between IPB D2 and IPB D3 cocks, as evidencedby the distribution of individual points in divergent directions in the cluster diagram. This phenomenonis indicative of disparities in selection pressure on body characteristics in the two strains. Significantly,during the starter period, a separate group of kampong hens formed at the top of the diagram, indicating the strong uniqueness of native chicken morphological characteristics and a body size pattern that is strikingly different from the IPB selection strain.